2019
DOI: 10.1097/shk.0000000000001152
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Importance of a Cytokine Network in Major Burns

Abstract: Major burns elicit an acute inflammatory response including various inflammatory cytokines. Cytokines play mutual interacting roles in inflammatory diseases. There is little evidence of the clinical significance of the cytokine network in patients with major burns. This study aimed to investigate the clinical significance of the cytokine network in patients with major burn. This prospective observational study comprising 38 patients with major burns (total body surface area (%TBSA) ≥ 20%) and 12 healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…Elevated levels of proinflammatory cytokines are associated with the clinical manifestations of CRS ( 15 , 16 ). For example, several cytokines in the sera of sepsis or burn patients are correlated with patient prognosis and disease severity ( 17 , 18 ). To explore the importance of the cytokine network in the pathogenesis of CRS, we reconstituted and reanalyzed the cytokine profiles of sera from CRS patients ( 17 , 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of proinflammatory cytokines are associated with the clinical manifestations of CRS ( 15 , 16 ). For example, several cytokines in the sera of sepsis or burn patients are correlated with patient prognosis and disease severity ( 17 , 18 ). To explore the importance of the cytokine network in the pathogenesis of CRS, we reconstituted and reanalyzed the cytokine profiles of sera from CRS patients ( 17 , 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, several cytokines in the sera of sepsis or burn patients are correlated with patient prognosis and disease severity ( 17 , 18 ). To explore the importance of the cytokine network in the pathogenesis of CRS, we reconstituted and reanalyzed the cytokine profiles of sera from CRS patients ( 17 , 18 ). A total of 91 patients with CRS associated with sepsis, acute respiratory distress syndrome (ARDS), or burns were enrolled in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Cytokine derangements are more severe in adult patients when compared with children and this heightened immunoinflammatory response has been suggested as a contributor to the increased morbidity and mortality observed in adults ( 87 ). Matsuura et al examined a cytokine network including monocyte chemoattractant protein-1 (MCP-1), IL-6, IL-8, and IL-10 and showed that cytokine derangements in burn patients with > 20% TBSA compared with healthy controls were correlated with burn injury severity and prognosis ( 90 ). When compared with non-burn trauma patients, patients with severe burns were found to have higher levels of IL-6 and IL-8 as early as 24 h after injury ( 91 ).…”
Section: Inflammatory Factorsmentioning
confidence: 99%
“…The inflammatory and hypermetabolic state that develops after burn injury persists following the acute phase ( 90 , 101 ). Nonsurvivors have significantly higher plasma levels of IL-1, IL-6, IL-10, IL-12, and TNF-α at 1 week from burn injury when compared with survivors ( 85 ).…”
Section: Inflammatory Factorsmentioning
confidence: 99%
“…Larger burns are also correlated with the systemic release of inflammatory cytokines, including interleukin 6 (IL-6), IL-8, IL-10, and monocyte chemoattractant protein 1 (MCP-1) (Bergquist et al, 2019). In a study of 38 patients with major burns, Hiroshi et al demonstrated that these four systemic inflammatory markers correlated with Sequential Organ Failure Assessment (SOFA) scores, while IL-6, IL-8, and IL-10 correlated with 28-day mortality (Matsuura et al, 2019). Finally, disruption of the skin barrier increases the susceptibility of the patient to infections caused by bacteria, fungus, and viruses.…”
Section: Overview Of Craniofacial Burn Wound Healingmentioning
confidence: 99%